PERLINDUNGAN HUKUM MASYARAKAT DALAM PANDEMI COVID 19 MELALUI VAKSIN SINOVAC - August Hamonangan (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
The Indonesian government has so far issued several policy packages aimed at tackling the spread of Covid-19, including PSBB, social distancing, physical distancing, health protocol rules (often washing hands with soap, increasing immunity, etc.), PPKM, and the Covid-19 vaccination program. This policy is also intensively carried out by various countries in the world. This research uses normative legal research methods, namely research conducted by selecting library materials or secondary data. The research conducted by the author is more aimed at the law approach and the case approach. The legal approach is carried out by examining the laws and regulations related to the issues being discussed. The form of legal protection for the public against the effects of post-covid-19 vaccination in Indonesia is in the form of preventive and repressive legal protection.